Perspektif Inklusif Pendidikan Agama Kristen terhadap Teks Kerja Pada Masyarakat Dawan di Nusa Tengara Timur - Iswanto Iswanto; Ferdinant Alexander (Sabda: Jurnal Teologi Kristen, 2020)
An inclusive perspective is conceptualized as the adaptation or internalization of the paradigm of a particular register into the intended concept. Christian education as a pedagogical concept is in a broad register, such as family, church and society. This study uses working text data on the Dawan community in an inclusive perspective on Christian education. The method used in this research is descriptive qualitative with a phenomenological approach. The results of the study explained that the working text of the Dawan community focused on the concept of monit naleko 'living well' as the main reference of the concept of 'work'. The inclusive perspective of Christian religious education is not necessarily adaptive to the reference. This non-adaptive emerges social interpretations and forms new concepts that are seen in attitudes and behavior. The novelty of research seen in the formulation of inclusive perspectives does not always refer to the adaptive renewal as previous research. Conceptual interactions can produce new concepts in social cognition. Strong internalization based on biblical interpretation must continue to be sought in the process of adaptive, inclusive perspective on Christian religious education. Key Words: inclusive perspective, Christian religious education, working texts.